Target Strength of encaged Atlantic redfish (Sebastes spp.) - Gauthier, Stéphane; Rose, George A. (ICES Journal of Marine Science, 2001)
Redfish ( Sebastes spp.) were caught at sea with feather hooks, kept alive in sea cages for >12 hours at 30 m depth, then transferred to cages at 10 m depth for another 12 h. Most fish survived this procedure in excellent condition. A total of 16 fish of length 24.5–30 cm were placed one at a time in an acoustically inert monofilament cage where target strength (TS) was measured for two hours using a 38 kHz split-beam echo-sounder. An underwater video camera enabled continuous monitoring of fish and cage. The best fit length based regression obtained from these data was TS=19 log [length (cm)]−66.6, in the standard format: TS=20 log [length (cm)]−68.1 (r2=0.18). TS varied by less than 4 dB over a range of tilt angles from −50° to 70° off dorsal aspect.